INFLUENCE OF GENDER ON THE INTENSITY OF INFLAMMATIVE RESPONSE IN INFLAMMATORY GALLBLADDER DISEASES - Spasovski, Zarko; Zafirova, Beti; Kirijas, Meri; Petrovska, Biljana Novevska; Stojanoski, Sasho; Krstevski, Stefan (Journal of Morphological Sciences, 2022)
Cholecystitis as an inflammatory reaction is recognized in symptomatic and asymptomatic form with or without complications. The aim is comparison of cholecystitis as an inflammatory process between the male and female population and proving a more intense inflammatory response in the male population. The study was conducted in the CGH "8th September" in the period 2019-2020. The collected data were analyzed with the statistical program SPSS Version 17.0. The research included and analyzed a total of 36 (n = 36) respondents who were divided into two groups. The first group of 17 (47.2%)  patients are male and the second group of 19 (52.8%) patients are female. Laboratory tests showed a significant difference between the two tested groups in the measured values of progesterone with a significance of p = 0.027 in favor of the female population, and for testosterone and IgA in favor of the male population (p = 0.001, p = 0.036, respectively), while in other markers examined no significant difference between the sexes was found.The influence of the hormonal factor on the intensity and character of the inflammatory changes is also shown by the values obtained from the laboratory tests in the study which showed a significant difference between the two groups in the measured values of progesterone with significance in favour of the female population, and for testosterone and IgA in favor of the male population, which proved the influence of the hormonal factor on the intensity and character of inflammatory changes. Keywords: cholecystitis, cytokines, estrogen, inflammation testosterone. https://doi.org/10.55302/JMS2251075s